2020
DOI: 10.3390/en13092131
|View full text |Cite
|
Sign up to set email alerts
|

Potential Map for the Installation of Concentrated Solar Power Towers in Chile

Abstract: This study aims to build a potential map for the installation of a central receiver concentrated solar power plant in Chile under the terms of the average net present cost of electricity generation during its lifetime. This is also called the levelized cost of electricity, which is a function of electricity production, capital costs, operational costs and financial parameters. The electricity production, capital and operational costs were defined as a function of the location through the Chilean territory. Sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…In addition, one of the highest solar radiation levels is observed in the Atacama Desert. The Cerro Dominador solar thermal plant is the first CSP plant in Latin America (Chile) and was built with a capacity of 110 MW [43].…”
Section: Pv Power Plants In Desertmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, one of the highest solar radiation levels is observed in the Atacama Desert. The Cerro Dominador solar thermal plant is the first CSP plant in Latin America (Chile) and was built with a capacity of 110 MW [43].…”
Section: Pv Power Plants In Desertmentioning
confidence: 99%
“…The project was finished in five phases, the first, second, third, fourth, and fifth phases, with 13 MW, 200 MW, 800 MW, 950 MW, and 900 MW of production capacity, respectively. PV technologies were used for the first, second, third, and fifth phases, but CSP and PV were used for the fourth phase [43].…”
Section: Pv Power Plants In Desertmentioning
confidence: 99%
“…A typical 50-MWe parabolic trough plant has a staff of 30 employees for plant operation and another 10 employees for solar field maintenance (IEA 2010). A recent study on the potential for CSP in Chile reported that a 130-MWe CSP power tower plant requires 40 employees-32 for operations and 8 for administrative work (Hernández et al 2020). The 110-MWe Crescent Dunes CSP power tower plant in Nevada reportedly requires 40 permanent workers for plant O&M (Hashem 2018).…”
Section: Future Oandm Costsmentioning
confidence: 99%
“…5 Concentrated solar power (CSP) systems comprise moving parts, increasing one-time cost, and recurring costs. 6 A concentrated solar photovoltaic system (CSPV) intensifies incident sunlight to increase cumulative transformation competence. 7 Various CSPV design methodologies have been invented 8 to efficiently transform photons into electrical energy, such as using the Fresnel lens to focus sunlight on solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…The efficiency of PV cells is linearly related to light intensity, but high temperatures lead to the degraded output 5 . Concentrated solar power (CSP) systems comprise moving parts, increasing one‐time cost, and recurring costs 6 . A concentrated solar photovoltaic system (CSPV) intensifies incident sunlight to increase cumulative transformation competence 7 .…”
Section: Introductionmentioning
confidence: 99%